THE IMPORTANCE OF EXERCISE IN TEACHING LOGICAL PROBLEM SOLVING - Munisa Aminovna Davlatova (Modern American Journals, 2025)
This article discusses the methods of solving logical problems related to work and productivity included in elementary school mathematics textbooks. The article considers a demonstrative method of solving logical problems. The differences in working with similar problems in the upper grades and elementary grades are shown.
Keywords: mathematics, logical, work, productivity, problem, demonstrativeness, analysis, synthesis, thinking, ability.